Preparation and in vivo absorption evaluation of spray dried powders containing salmon calcitonin loaded chitosan nanoparticles for pulmonary delivery - Sinsuebpol, Chutima (Dove Medical Press, 2013)
PURPOSE: The aim of the present study was to prepare inhalable co-spray dried powders of salmon calcitonin loaded chitosan nanoparticles (sCT-CS-NPs) with mannitol and investigate pulmonary absorption in rats. METHODS: The sCT-CS-NPs were prepared by the ionic gelation method using sodium tripolyphosphate (TPP) as a cross-linking polyion. Inhalable dry powders were obtained by co-spray drying aqueous dispersion of sCT-CS-NPs and mannitol. sCT-CS-NPs co-spray dried powders were characterized with respect to morphology, particle size, powder density, aerodynamic diameter, protein integrity, in vitro release of sCT, and aerosolization. The plasmatic sCT levels following intratracheal administration of sCT-CS-NPs spray dried powders to the rats was also determined. RESULTS: sCT-CS-NPs were able to be incorporated into mannitol forming inhalable microparticles by the spray drying process. The sCT-CS-NPs/mannitol ratios and spray drying process affected the properties of the microparticles obtained. The conformation of the secondary structures of sCTs was affected by both mannitol content and spray dry inlet temperature. The sCT-CS-NPs were recovered after reconstitution of spray dried powders in an aqueous medium. The sCT release profile from spray dried powders was similar to that from sCT-CS-NPs. In vitro inhalation parameters measured by the Andersen cascade impactor indicated sCT-CS-NPs spray dried powders having promising aerodynamic properties for deposition in the deep lung. Determination of the plasmatic sCT levels following intratracheal administration to rats revealed that the inhalable sCT-CS NPs spray dried powders provided higher protein absorption compared to native sCT powders. CONCLUSION: The sCT-CS-NPs with mannitol based spray dried powders were prepared to have appropriate aerodynamic properties for pulmonary delivery. The developed system was able to deliver sCT via a pulmonary route into the systemic circulation.